Design and testing of multischeme horizontal joints for prefabricated two-walls-in-one diaphragm wall. (May 2023) - Qiu, Tong; Zhang, Jiqing; Chen, Xiangsheng; Xu, Zhenyan; Su, Dong; Song, Ran; Cui, Tao
Abstract: There are obvious technical defects and resource wastage related to cast-in-situ diaphragm walls. To overcome these problems, this study presents a novel prefabricated two-walls-in-one diaphragm wall (PTDW) and a horizontal joint design method. First, full-scale experiments on multischeme PTDW horizontal joints and prefabricated walls were conducted. Second, a design method for PTDW horizontal joints was developed. Finally, the key design parameters for the joints were determined through a parametric analysis. The main conclusions are as follows. First, the mechanical properties of the welded joint (WJ) were better than the prefabricated wall. Bolted joints and grouted joints (BJ and GJ) may be damaged before the prefabricated walls. Second, the proposed design method promoted an excellent performance of WJ far superior to that of the BJ and GJ. Third, one compressive interface is the core factor and most efficient for the joints' bending resistance. Small-tenon joints with a maximized compressive interface achieved maximum performance. Finally, fasteners are the core factors of the joints' bearing capacity and stiffness properties. Therefore, WJ are recommended to easily form a rigid joint with a small-tenon scheme. This study provides a parameterized joint design method, which has high application value for green construction.